Collaborative Work in the management of congenital facial malformations. - Laquihuanaco Loza, Felipe Santiago (2022)
The health services system in Peru is fragmented and segmented, in this new century a coordinated and cooperative attitude is required among health professionals. Lip alveolus-palatine malformations are the most frequent congenital anomalies on the bucomaxillofacial region, affecting the growth and development of orofacial structures of two-thirds of the face, altering innate oral reflexes such as biting, sucking, swallowing and the capacity on the cavity buccal to allow pressure build-up. Adequate performance in health service is achieved with a shared vision and posture among the members of the work team, added to effective management, for which interprofessional collaborative practice requires paradigm changes, in which evidence is demonstrated substantial and irrefutable of a team culture and a reliable interdisciplinary environment, recognizing shared responsibility for results.